2019
DOI: 10.1002/cpt.1706
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐B*51:01 and CYP2C9*3 Are Risk Factors for Phenytoin‐Induced Eruption in the Japanese Population: Analysis of Data From the Biobank Japan Project

Abstract: CYP2C9*3 and HLA-B alleles are reportedly associated with phenytoin-induced eruption in some East Asian populations; however, this finding is not readily applicable to the Japanese population. Thus, we aimed to investigate the risk alleles using samples and data from BioBank Japan. A total of 747 patients (24 cases and 723 tolerant controls) were selected for analysis. Case-control association studies were conducted, using CYP2C9*3, CYP2C9*27, CYP2C19*2, CYP2C19*3, and HLA-B allele genotype data. CYP2C9*3 carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The combined assessment of the risk of HLA and CYP2C9 alleles is useful for predicting PHT-induced SCAR in selected Asian populations ( Cheung et al., 2013 ; Chang et al., 2017 ; Su et al., 2019 ). A recent study from Japanese research groups showed that a combination of CYP2C9*3 and HLA‐B*51:01 was associated with PHT-induced hypersensitivity reactions in Japanese population ( Hikino et al., 2019 ). Previously, other study indicated other metabolizing enzyme, CYP2B6, genetic variant involved in nevirapine-induced SJS/TEN.…”
Section: Drug Hypersensitivity and Genetic Susceptibility Markersmentioning
confidence: 99%
“…The combined assessment of the risk of HLA and CYP2C9 alleles is useful for predicting PHT-induced SCAR in selected Asian populations ( Cheung et al., 2013 ; Chang et al., 2017 ; Su et al., 2019 ). A recent study from Japanese research groups showed that a combination of CYP2C9*3 and HLA‐B*51:01 was associated with PHT-induced hypersensitivity reactions in Japanese population ( Hikino et al., 2019 ). Previously, other study indicated other metabolizing enzyme, CYP2B6, genetic variant involved in nevirapine-induced SJS/TEN.…”
Section: Drug Hypersensitivity and Genetic Susceptibility Markersmentioning
confidence: 99%
“…11,20 Recent evidence suggests that the CYP2C9*3 variant may also be associated with increased risk for cutaneous adverse drug events independently of HLA-B genotype. 9,10,[21][22][23] These studies were conducted primarily in Asian populations where the CYP2C9*2 variant is absent and the HLA-B*15:02 allele is common. Therefore, we sought first to determine the association of both CYP2C9*2 and CYP2C9*3 with phenytoin-induced cutaneous adverse events in a large, multi-ethnic cohort where genotype was unknown throughout treatment.…”
Section: What Does This Study Add To Our Knowledge?mentioning
confidence: 99%